(3GbJUGOjGJ GdJLGQI GdNGQLjIs - (3eMeO CMeO(B, (3GdSQjJjs ((3GdGScfOQjI(B:s (3eDSSI QFjI(B,s, 2008)
(3eGgjI GdJLGQI GdNGQLjI,GdfXQjI GdcdGSjcjI aj GdJLGQI GdOhdjI,GdfXQjI GdMOjKI aj GdJLGQI GdOhdjI,JMOjO eYOd GdJHGOd GdOhdj hTQhW GdJLGQI,SjGSI GdMQjI GdJLGQjI,SjGSI GdMeGjI,GdJcGed GdGbJUGOj,ejRGf GdeOahYGJ GdOhdjI,SYQ GdUQa,GdJLGQI GdGdcJQhfjI hOhQgG aj GdJLGQI GdOhdjIs
(3HHdjhZQGajG(B:(3U(B.320s
Keywords: (3GdEbJUGOs; (3GdJLGQI GdNGQLjIs